PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STAD BERBASIS KONTEKSTUAL TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIKA SISWA KELAS IX SMPN 1 BATUSANGKAR - Syafriadi, Amri; Adripen, Adripen; Maris, Ika Metiza (Jurnal Pembelajaran MIPA, 2014)
The purpose of this research was to know mathematics communication bility of students with cooperative learning model type STAD based contexstual at class IX SMPN 1 Batusangkar. The study was quasi eksperimental research with the draft of research was Randomized Control Group Only Design. The subject of this research obtained from the final test. The hypothesis of this research was tested by MIINITAB program named t-test one way. The results showed a difference in mean value, variance and standard deviation in the second grade sample. From the result of t-test, research obtained that p-value 0, so the hypothesis of this research is accepted at taraf signifikan Î± = 0.05. So, concluded that the mathematics communication ability of students was by applaying of cooperative learning model type STAD based contexstual higher than students in conventional leraning.Keywords:Â Cooperative type STAD, approach contextual, Mathematics Communication Ability